Application research of nanovideo creation technology in modern art. (30th September 2020) - Yu, Chunlin; Mu, Bo; Li, Xiao; Xu, Qian; Fang, Xi
Nanomaterials are one of the new materials in the 21st century. When the size of the materials is at the nanometre level, they exhibit special physical and chemical properties that macromaterials cannot. At present, nanoproduct design has been widely used in many fields and shows unique performance advantages of nanoproducts. As the most promising material, it has characteristics that are difficult to achieve with ordinary materials. This paper introduces the special properties of nanomaterials, and lays the foundation for product case analysis. Nanoart is a branch of science and art derived from the development of nanotechnology in recent years. Since the development of this discipline is only a few years old, many related concepts and terms are not mature enough and have not been widely recognised by the industry. The paper analyses the definition of nanoart, art forms, and the concepts and words related to nanoart such as DNA art. Finally, the connotation of computer-assisted nanoart is also discussed. As an important form of nanoart, nanovideo has achieved rapid development in recent years. The level of creation of nanovideo works depends on people's understanding of the world of micro-nano, which is directly related to nanotechnology and computer technology. This paper gives the definition and classification of nanovideo art, introduces the creation method of nanovideo, and finally gives a brief description of nano online games in nanovideo.